PELATIHAN BAHASA ISYARAT DI LINGKUP SENTRA WIRAJAYA DI MAKASSAR DALAM MEMBANGUN KOMUNIKASI EFEKTIF KEPADA TUNARUNGU (TULI) - Irdianti Irdianti; Muh. Nur Haq I.S. Mannessa, Nailah Ramadhani Muchsin, Andi Afifah Andranatha (Adiba Aisha Amira, 2022)
Communication that exists between rehabilitation staff at the Wirajaya Center in Makassar and deaf PPKS (Recipients of Social Welfare Services) can be said to be ineffective due to a lack of understanding by rehabilitation staff regarding sign language. This sign language training aims to help rehabilitation staff at the Wirajaya Center in Makassar to communicate with PPKS for the Deaf. The training implementation method used is training and mentoring with an active participatory strategy. This training was carried out in 2 sessions, namely November 24-25 at the Wirajaya Pettarani Sentra and November 28-29 2022 at the Salodong Wirajaya Sentra. The results of this training show that the rehabilitation staff who are participants already know and understand the signs of the alphabet and other words, from knowing only 1 to 2 words to knowing a few words. Participants were also able to practice using sign language after being given material and using sign language in providing interventions for Deaf PPKS.